Compilation of Islamic Law as the Foundation for Education in the Context of Religious Life - Febriansyah, Ferry Irawan (EDUKASI: Jurnal Pendidikan Islam, 2017)
Education is the most important part in shaping the character of the nation. The character of the nation if balanced with education, then the human resources will show the expected quality. Compilation of Islamic law, providing education in the field of law related to Islam, so that the younger generation understands the importance of Islamic law in running the life of nation and state. Islamic education is the most important thing for the young generation to maintain and preserve the understanding of law related to Islam. Understanding law does not mean just science, but as knowledge that must be known to the nationÃ¢â¬â¢s generation. Compilation of Islamic law becomes the civil foundation for Muslims in carrying out related contracts of marriage, inheritance and endowment. The compilation of Islamic law is expected to provide a basis for education and knowledge for young people, especially academics in deepening Islamic civil law listed in the compilation of Islamic law.